(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Determine the rate of dysmenorrhea and survey the level of dysmenorrhea in female medical students of Dai Nam University. Subject and method: Cross-sectional study on 152 female medical students of courses YK14, YK15, YK16, YK17, YK18 at Dai Nam University. Results: The rate of pain during the menstrual cycle was 75.6%, in which the two common pain locations were lower abdominal pain and back or pelvic pain. The average pain level before menstruation was 2.98 ± 1.41, lower than the pain level during menstruation 3.96 ± 1.39. The signs of abdominal pain during the menstrual cycle, before menstruation and the level of pain during menstruation, before menstruation affected the lives of the study subjects. Conclusion: The study suggests that more attention should be paid to menstruation and menstrual-related disorders in female medical students in the future.